Removal of Methylene Blue of Textile Industry Waste with Activated Carbon using Adsorption Method - Maryudi Maryudi; Shinta Amelia; Siti Salamah (Reaktor, 2019)
The colorant that is often used in the textile industry is methylene blue which is a cationic heterocyclic aromatic compound. This compound is very stable and is difficult to decompose naturally leading to environment in large concentrations. Therefore, a waste treatment technology to reduce the concentration of dye waste in water becomes importannt. So far, adsorption method with activated carbon remains the most efficient and effective technique in removing dyes from liquid waste due to its relatively large adsorption capacity. Activated carbon is one of the non-metallic mineral commodities or multipurpose industrial minerals, one of which is as an adsorbent or adsorbent media. This study aims to determine the potential of activated carbon in adsorbing methylene blue with variations in the concentration of methylene blue and particle size of activated carbon. The procedures in this experiment include, the preparation of activated carbon with size variations (20-60, 60-100 and> 100 mesh) and variations in the concentration of methylene blue (15 ppm, 30 ppm and 45 ppm) with contact time (0 to 180 minutes). From the results of the study, it was found that the smaller the size of activated carbon used, the greater the adsorption capacity, ie at mesh size> 100 mesh, the adsorption capacity was 9.8%. Whereas, the smaller the concentration of methylene blue, the activated carbon could work optimally at a concentration of 15 ppm at 30 minutes with adsorption capacity as high as 100%.Keywords: adsorption; Methylene Blue; activated carbon; concentration; time; particle size